Impact of Relocating the National Capital on the Projection of Electrical Energy Consumption: a Case Study in East Kalimantan Province, Indonesia - Yofinda E Setiawan; Kusnanto Kusnanto; Ahmad A Setiawan (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
The availability of electrical energy is one of the crucial parameters in the growth and development of a region. To accelerate Indonesia's economic transformation and change the orientation of development to become Indonesia-centric, the government will move the current capital city to the province of East Kalimantan. Various policies have been drawn up, including the plan to relocate civil servants. The increase in population and economic mobility will have an impact on the demand for electrical energy. This research uses LEAP software, where the approach method used to calculate the projected electrical energy demand is the end-use method. There are three scenarios for projecting electricity demand, that is business as usual (BAU), moderate scenario (MOD), and optimistic scenario (OPT). MOD and OPT are scenarios with the impact of moving the national capital. The projection results for the 2022-2035 period show that the consumption of electrical energy in each scenario increases every year. The BAU scenario grew by 8.11%, the MOD scenario by 9.09%, and the OPT scenario by 9.64%. Cumulative energy consumption for all customer sectors in 2035 in the BAU scenario will reach 13,760 GWh. The MOD scenario is 15,899 GWh, and the highest energy consumption in 2035 is in the OPT scenario which reaches 17,171 GWh.